(untitled) (Research, Society and Development, 2026)
Food colorants play a fundamental role in the visual attractiveness of foods, directly influencing consumer acceptance and choice. These additives are classified as natural and artificial, differing in origin, chemical properties, stability, and impacts on human health. Artificial colorants, obtained through chemical synthesis, stand out for their high coloring power, low cost, and strong stability under variations of pH, light, and temperature; however, their consumption has been associated with potential adverse effects, such as allergic reactions, childhood hyperactivity, and possible toxicological damage, especially when ingested cumulatively. This scenario becomes even more concerning in the context of foods intended for children, considering their greater physiological vulnerability to chemical exposure. In contrast, natural colorants, extracted from plant and animal sources such as annatto, anthocyanins, betalains, carotenoids, turmeric, and chlorophyll, present lower toxicological potential and, in some cases, beneficial functional health properties, although they still face challenges related to stability, cost, and industrial application. The present study consists of a bibliographic review of scientific literature, including articles, theses, and national and international regulations published between 2008 and 2024, aiming to analyze regulatory, toxicological, and industrial aspects of food colorants, with emphasis on children’s consumption. It also highlights regulatory updates conducted by the Brazilian Health Regulatory Agency (ANVISA), aligned with Codex Alimentarius guidelines. It is concluded that the replacement of artificial colorants with natural alternatives is a promising trend, aligned with food safety, public health, and sustainability.